THE EFFECT OF ONLINE ADVERTISING AND E-WOM ON ONLINE PRODUCT PURCHASE DECISIONS (STUDY ON CONSUMER BAG STORE MANADO) - Venandito Tuyu; Silcyljeova Moniharapon; Jane Grace Poluan (Universitas Sam Ratulangi, 2022)
The rapid development of information technology, including the internet, has had a great impact in various aspects, including the development of the business and marketing world. The business sector is the sector that is most rapidly affected by the development of information technology and telecommunications. High human mobility requires the business world to be able to provide services and goods quickly according to consumer demand. To overcome this problem, transactions are now emerging that use the internet to connect producers and consumers. Online shopping or online shopping via the internet is a process of buying goods or services from a seller who makes the selling process via the internet. This study aims to determine the effect of online advertising and electronic word of mouth on consumer purchasing decisions. The analytical method used is multiple linear regression. The results of the hypothesis test found that simultaneously online advertising and E-WOM have an effect on purchasing decisions, but partially online advertising has no effect on consumer purchasing decisions. For Bag Store Manado in order to maintain and improve the existing E-WOM factor, and it is necessary to pay more attention to the Online Advertising that is applied so that it can help improve Purchase Decisions.